National Institute of Allergy and Infectious Diseases, NIH Volume 3: Intramural Research - Georgiev, Vassil St (Infectious Disease, 2010)
National Institute of Allergy and Infectious Diseases, NIH: Volume III: Intramural Research contains a broad overview of the research activity of the NIAID intramural scientists working in the Division of Intramural Research (DIR) and the Vaccine Research Center (VRC), both in the Bethesda campus, and the Rocky Mountains Research Laboratories. Each of these laboratories employs scientists internationally recognized as leaders in their fields of biomedical research. This volume focuses on individual research contributions by internationally known scientists doing research in the NIAID laboratories.